“Mainly, José de Acosta deserves to be read and recommended”: the apropriation of the idea of the mission by the Dutch reformed theologian Johannes Hoornbeeck - Murguía, Luis Alberto Martin Dávila (Revista de História, 2023)
The article discusses the relation between the Spanish Jesuit José de Acosta (1540-1600) and the Dutch Reformed theologian Johannes Hoornbeeck (1617-1666). Distant for the time they lived, for the spaces where they developed their action and for the very creed they professed, these two religious achieved an important reflection on the role of the Christian mission in territories of barbarians and pagans. In a period of strong political and religious disputes between Catholics and Protestants, the analysis of Hoornbeeck’s main text allows us to better understand a delicate process of appropriation and re-elaboration of the idea of mission within the parameters of the Dutch reformed dogma carried out from the Peruvian problematic by the Jesuit Acosta.